Structure, mechanism and cooperation of bacterial multidrug transporters. (August 2015) - Du, Dijun; van Veen, Hendrik W; Murakami, Satoshi; Pos, Klaas M; Luisi, Ben F
Highlights: Structure-based mechanisms are available for five major classes of multi-drug transporters. Three transporter classes form tripartite assemblies spanning the bacterial cell envelope. The structure of a tripartite assembly provides mechanistic insight into these complex machines. The different classes of transporters act as a system to transport a chemically broad range of drugs. Abstract : Cells from all domains of life encode energy-dependent trans-membrane transporters that can expel harmful substances including clinically applied therapeutic agents. As a collective body, these transporters perform as a super-system that confers tolerance to an enormous range of harmful compounds and consequently aid survival in hazardous environments. In the Gram-negative bacteria, some of these transporters serve as energy-transducing components of tripartite assemblies that actively efflux drugs and other harmful compounds, as well as deliver virulence agents across the entire cell envelope. We draw together recent structural and functional data to present the current models for the transport mechanisms for the main classes of multi-drug transporters and their higher-order assemblies.